Development of fuzzy logic controller for maximum power point tracking technique of photovoltaic system - Alhamdawee, Ehsan Mohsin Obaid; Mailah, Nashiren Farzilah; Mohd Radzi, Mohd Amran; Shafie, Suhaidi (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
Photovoltaic system has nonlinear characteristics that are affected by the environmental conditions. The photovoltaic voltage and current have nonlinear changes with the variations of irradiation and temperature. These continuous changes of photovoltaic voltage and current prevent the solar model from working at maximum power efficiently. Thus, the situation imposes the use of techniques that enables the solar system to work at its maximum power. The conventional techniques such as perturb and observe (P&O) has some drawbacks such as continuous oscillation around the maximum power point (MPP), slow convergence toward the maximum power point at steady state conditions and wrong tracking decisions at low irradiance levels. This paper presents a fuzzy logic controller (FLC) that eliminates or reduces the drawbacks of the conventional technique in terms of oscillation, minimum time to reach maximum power point and stability.